If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.5(x + -2) = 7(x + -4) Reorder the terms: 2.5(-2 + x) = 7(x + -4) (-2 * 2.5 + x * 2.5) = 7(x + -4) (-5 + 2.5x) = 7(x + -4) Reorder the terms: -5 + 2.5x = 7(-4 + x) -5 + 2.5x = (-4 * 7 + x * 7) -5 + 2.5x = (-28 + 7x) Solving -5 + 2.5x = -28 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -5 + 2.5x + -7x = -28 + 7x + -7x Combine like terms: 2.5x + -7x = -4.5x -5 + -4.5x = -28 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 + -4.5x = -28 + 0 -5 + -4.5x = -28 Add '5' to each side of the equation. -5 + 5 + -4.5x = -28 + 5 Combine like terms: -5 + 5 = 0 0 + -4.5x = -28 + 5 -4.5x = -28 + 5 Combine like terms: -28 + 5 = -23 -4.5x = -23 Divide each side by '-4.5'. x = 5.111111111 Simplifying x = 5.111111111
| 48-3x-33-x=7 | | (Y+4)(Y+4)=36 | | 5/4*r=20 | | x^2+5x+210=0 | | http://media.education2020.com/EVresources/2003-03-01-00-00_vl_files/i0080001.jpg | | 2x-3+7x+3=180 | | 34-22=20+14 | | 1x+5=1x+7 | | Y=7/2×-5 | | 2*cosx^2-cosx-1=0 | | 2x-3+7x-3=189 | | P/-8-7=11 | | S+(4s+6)=26 | | -5x+3=2(x-9) | | -22+19c=15 | | X+50+115=180 | | 2x-3=7x-3 | | j-0.2=0.8 | | 6(5x+5)=300 | | 2(x+4)+5x=64 | | 79-y=2y+22 | | N/2-7=-45 | | 2(x+4)+5x=-32 | | a^2-7ab+10b^2= | | 8+10+4y+2=60 | | 5(X-8/5)=5x+ | | 4x+1+2x=1 | | 8-15=41 | | 12=-6x+8x | | 49u-64= | | 5x-3y-13=0 | | X(x-1)(2x-3)=0 |